PENGARUH JARAK LUBANG INOKULASI TERHADAP KESEMPURNAAN PEMBENTUKAN RESIN PADA POHON GAHARU (Aquilaria filaria) DI DESA URSANA. KABUPATEN SERAM BAGIAN BARAT - Seivra Henderina Noya; Johan M. Matinahoru; Ludia Siahaya (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
Agarwood (Aquilaria filaria) is a high-value non-timber forest product whose resin formation can be induced through inoculation with the fungus Fusarium oxysporum. The success of resin induction is influenced by several factors, including the spacing between inoculation holes. This study aimed to analyze the effect of inoculation hole spacing on resin formation in A. filaria. The research was conducted in Ursana Village, Inamosol District, West Seram Regency, from March to June. A factorial Completely Randomized Design (CRD) was employed with two factors: vertical inoculation spacing (10 cm and 15 cm) and horizontal inoculation spacing (2 cm, 4 cm, and 6 cm). The observed parameters included the degree of infection zone formation, infection zone area, wood tissue color, and agarwood aroma. Data were analyzed using analysis of variance (ANOVA), followed by Tukey’s Honestly Significant Difference (HSD) test at a 95% confidence level, while qualitative data were analyzed using the Friedman test. The results showed that inoculation hole spacing significantly affected the infection zone area, wood tissue color, and agarwood aroma. The combination of 10 cm vertical spacing and 2 cm horizontal spacing produced the largest infection zone area (25.70 cm²), dark brown wood discoloration, and a clearly detectable characteristic agarwood aroma. This treatment also exhibited the highest degree of infection zone fusion between inoculation holes, reaching 20.68%. These findings indicate that closer inoculation hole spacing, particularly the combination of 10 cm vertical spacing and 2 cm horizontal spacing, is more effective in promoting agarwood resin formation in Aquilaria filaria.